The American Revolution : a Very Short Introduction - Allison, Robert J. (Very short introductions., 2015)
Between 1760 and 1800, the people of the United States created a new nation, based on the idea that all people have the right to govern themselves. This introduction recreates the experiences that led to the Revolution; the experience of war; and the post-war creation of a new political society.